Ad Petr. Sat. fr. 16 Müller - Zeltchenko, Vsevolod (Hyperboreus, 2016)
In a fragment of Petronius (fr. 16 Müller) certain persons are mentioned that used to duck their heads when passing through the Neapolitan tunnel (crypta Neapolitana) between Puteoli and Naples. According to some interpretations proposed in the last decade, this is a realistic detail proving that the vault of the tunnel was low (yet the measuring of modern archaeologists and geotechnical engineers proves that this structure was originally at least 3,5 to 4 m high, though it had subsequently changed in course of reconstructions in the 15th–20th centuries). F. R. Berno sees in the fragment a reference to some apotropaic practice, otherwise unknown. Scholars often assume that the characters of Satyricon travelled through the Neapolitan tunnel on some occasion. Meanwhile the right way of understanding the fragment was indicated in 1999 by M. Hascher: this is a biting hyperbole typical of Petronius. Hascher considers two possibilities: either arrogant and lofty persons are mocked that seem so tall to themselves as to  bend their heads in a huge tunnel; or extremely timid and cautious people are meant who stoop instinctively as they enter the dark vaults. The author supports the ﬁrst version adducing parallels to Petronius’ joke, namely a fragment of Crassus’ speech in Cicero (Cic. De or. 2. 267 = Crass. fr. 21 Malcovati) and a description of Constantius entering Rome in a solemn procession (Amm. Marcell. 16. 10. 10).